2022
DOI: 10.1016/j.xops.2022.100119
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Differentiation of Bacterial and Fungal Keratitis Using Deep Convolutional Neural Networks

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…There is currently no point of care test for fungal keratitis and this remains a major obstacle in improving health outcomes for the condition. Artificial intelligence (AI) based on deep learning techniques has demonstrated promising performance in detecting microbial keratitis and differentiating between fungal, bacterial and viral causes when using slit-lamp or smartphone images, outperforming even specialist clinicians [ 38 ]. The utilisation of AI could overcome the need for highly trained operators and specialized equipment, which limits the use of many of the other diagnostic alternatives in low-resource settings.…”
Section: Diagnosismentioning
confidence: 99%
“…There is currently no point of care test for fungal keratitis and this remains a major obstacle in improving health outcomes for the condition. Artificial intelligence (AI) based on deep learning techniques has demonstrated promising performance in detecting microbial keratitis and differentiating between fungal, bacterial and viral causes when using slit-lamp or smartphone images, outperforming even specialist clinicians [ 38 ]. The utilisation of AI could overcome the need for highly trained operators and specialized equipment, which limits the use of many of the other diagnostic alternatives in low-resource settings.…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, DL-based models have demonstrated good accuracy in differentiating the underlying cause of IK, particularly between bacterial and fungal keratitis (Hung et al, 2021 ; Redd et al, 2022b ), which is a common diagnostic dilemma in clinical practice. Redd et al ( 2022b ) recently evaluated five convolutional neural networks using images of culture-proven IK obtained from handheld cameras and reported a higher diagnostic accuracy of the CNN-based DL models when compared to cornea experts (area under the ROC = 0.84 vs. 0.76).…”
Section: Potential Solutions For Improving Diagnostic Performancementioning
confidence: 99%
“…In addition, DL-based models have demonstrated good accuracy in differentiating the underlying cause of IK, particularly between bacterial and fungal keratitis (Hung et al, 2021 ; Redd et al, 2022b ), which is a common diagnostic dilemma in clinical practice. Redd et al ( 2022b ) recently evaluated five convolutional neural networks using images of culture-proven IK obtained from handheld cameras and reported a higher diagnostic accuracy of the CNN-based DL models when compared to cornea experts (area under the ROC = 0.84 vs. 0.76). Another study has also shown the ability of a CNN-based DL model in accurately distinguishing between corneal scars and IK (Tiwari et al, 2022 ), which serves as a useful and inexpensive system to aid the triage, assessment, initiation and cessation of antimicrobial therapy for IK in regions with limited access to eye care.…”
Section: Potential Solutions For Improving Diagnostic Performancementioning
confidence: 99%
“…The rapid identification of Pseudomonas keratitis from suspected BK is critical to prevent corneal ulcer patients from corneal melting and blindness. Diagnosing BK from MK via the DL approach of external eye photos has recently shown promise [ 8 , 9 , 10 , 17 ]. Still, there is no report exploring the potential of DL models for further differentiating BK into Pseudomonas and non- Pseudomonas keratitis to date.…”
Section: Discussionmentioning
confidence: 99%